Manfaat Pengembangan Pariwisata Kiara Artha Park Terhadap Kehidupan Masyarakat Sekitar - Clarisa Yuniar Bahri; Relanda Nur Aidil Fitri (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research was conducted to determine the effect of tourism development in Kiara artha park on the lives of local people in the tourism area, how the influence felt by local people. Some of the analysis methods used are descriptive methods. It is very important the role of open space for people’s lives, therefore the Bandung City Government carried out the construction of this city park. This can also attract people to be able to utilize this city park as a public space. The presence of Kiara Artha Park which is one of the city parks in Bandung is utilized by the community to carry out various activities in the park.